A quantum dynamical study of the photoelectron spectra and the Renner-Teller effect in BrCN and ClCN based on four-component potential energy hypersurfaces - Tran, Van Anh; Pernpointner, Markus (Chemical physics, 2018)
In this work we investigate the Renner-Teller effect (RTE) in the photoelectron spectra of ClCN and BrCN. The spectra were calculated by a nuclear wave packet propagation on coupled cationic Π1/2/Π3/2 surfaces obtained by the four-component Fock-space coupled cluster method. The scalar relativistic, spin-orbit and electron correlation effects are consistently included in the hypersurfaces for the three internal nuclear degrees of freedom. In contrast to other approaches no coupling matrix elements involving the spin-orbit operator together with an explicit representation of the wave function were necessary. The current study extends earlier work on the RTE for the derivation of the Renner-Teller parameters c and d where only one nuclear degree of freedom was considered (Pernpointner and Salopiata, 2013). The outlined procedure is especially useful for electronic structure methods that yield accurate energies but do not provide an explicit wave function representation.